PERCENTAGES OF CARCASS PARTS OF MALE LOCAL DUCKS FED TORCH GINGER FLOWER (Etlingera elatior) SOLUTION INCLUDED IN COMMERCIAL RATION - Wahyan, Dwiki Tri Satya; Handarini, Ristika; Kardaya, Dede (Jurnal Peternakan Nusantara, 2017)
Breast and thigh are the parts of duck carcass which are most commonly utilized and consumed by people.  These carcass parts consist of meat, skin, and bones.  This study was aimed at assessing the effects of the inclusion of torch ginger flower solution in commercial ration on live weight and percentages of carcass and its parts of male local ducks.  The study was conducted from June to August 2016 at Poultry Laboratory of Animal Science Study Program, Faculty of Agriculture, Djuanda University, Bogor.  Twenty-four male local ducks aged 2 weeks with average initial body weight of 450 ± 53.04 g were used.  A completely randomized design with 4 treatments and 3 replicates was used.  Treatments consisted of commercial ration + 0% torch ginger flower solution (R0), commercial ration + 2.5% torch ginger flower solution (R1), commercial ration + 5.0% torch ginger flower solution (R2), and commercial ration + 7.5% torch ginger flower solution (R3).  Measurements were taken on the percentages of whole breast, breast meat, breast bones, whole thigh, thigh meat, and thigh bones.  Data were subjected to an analysis of variance and a Duncan test.  Results showed that treatments gave significant effect (P<0.05) on the percentage of thigh meat.  The inclusion of torch ginger flower solution in ration did not negatively affect carcass parts of male local ducks.  The inclusion of 7.5% torch ginger flower solution in commercial ration increased the percentage of whole breast.  It was also found that the inclusion of 5.0 and 7.5% torch ginger flower solution in commercial ration increased the percentage of thigh meat.Key words: torch ginger flower solution, male local duck, carcass parts